2005
DOI: 10.1121/1.2082567
|View full text |Cite
|
Sign up to set email alerts
|

Informational masking of speech in children: Effects of ipsilateral and contralateral distracters

Abstract: Using a closed-set speech recognition paradigm thought to be heavily influenced by informational masking, auditory selective attention was measured in 38 children (ages 4-16 years) and 8 adults (ages 20-30 years). The task required attention to a monaural target speech message that was presented with a time-synchronized distracter message in the same ear. In some conditions a second distracter message or a speech-shaped noise was presented to the other ear. Compared to adults, children required higher target/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
174
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 54 publications
31
174
3
Order By: Relevance
“…By perhaps 8 or 9 years of age, children's auditory sensitivity and their ability to separate sounds even under quite complex listening conditions are similar to adults' (e.g., Hall, Buss, Grose, & Dev, 2004;Wightman & Kistler, 2005). Nonetheless, Hazan and Barrett (2000) have reported that children as old as 12 years of age are less consistent than adults in their identification of consonants.…”
Section: Flexibility In the Use Of Acoustic Informationmentioning
confidence: 95%
See 1 more Smart Citation
“…By perhaps 8 or 9 years of age, children's auditory sensitivity and their ability to separate sounds even under quite complex listening conditions are similar to adults' (e.g., Hall, Buss, Grose, & Dev, 2004;Wightman & Kistler, 2005). Nonetheless, Hazan and Barrett (2000) have reported that children as old as 12 years of age are less consistent than adults in their identification of consonants.…”
Section: Flexibility In the Use Of Acoustic Informationmentioning
confidence: 95%
“…Distraction by irrelevant sounds may be worse than that seen in adults in children as old as 10-years of age, but by 7 or 8 years, children can overcome such distraction effects as well as adults can when they are given a cue like onset time to distinguish the target sound from the distracter (Leibold & Neff, under review). As late as 6-8 years, children generally perform more poorly than adults in dichotic listening tasks (Cherry, 1981;Pearson & Lane, 1991;Wightman & Kistler, 2005), suggesting that auditory selective attention continues to improve into this age range. The studies examining these age-related changes in behavior have all been cross-sectional studies, but there is little indication that these auditory skills develop very gradually.…”
Section: Increasing Specificitymentioning
confidence: 99%
“…We were also interested in examining age effects within populations of children with NH or BiCIs. Although NH children are able to use spatial cues for source segregation, developmental effects have been reported in free field Yuen and Yuan, 2014) and for contralateral unmasking headphone stimulations (Wightman and Kistler, 2005). This difference could be due to the fact that informational masking also depends on development of central auditory mechanisms and nonauditory factors such as attention (Leibold and Bonino, 2009;Lutfi et al, 2003;Wightman et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Despite evidence of greater susceptibility to informational masking in school-age children than adults, both groups benefit from the introduction of segregation cues, including spatial separation of the target and masker (Litovsky, 2005;Yuen and Yuan, 2014), introduction of a sex mismatch between the target and masker (Wightman and Kistler, 2005;Misurelli and Litovsky, 2015), and mismatches in the target and masker language (Calandruccio et al, 2016). Greater susceptibility to informational masking has been interpreted as indicating that adults are better than children at segregating the auditory streams associated with the target and masker talkers, and/or selectively attending to the target.…”
Section: Introductionmentioning
confidence: 99%